2020
DOI: 10.1038/s41467-020-17585-8
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerols sequester monotopic membrane proteins to lipid droplets

Abstract: Triacylglycerols (TG) are synthesized at the endoplasmic reticulum (ER) bilayer and packaged into organelles called lipid droplets (LDs). LDs are covered by a single phospholipid monolayer contiguous with the ER bilayer. This connection is used by several monotopic integral membrane proteins, with hydrophobic membrane association domains (HDs), to diffuse between the organelles. However, how proteins partition between ER and LDs is not understood. Here, we employed synthetic model systems and found that HD-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 70 publications
(135 reference statements)
6
57
0
Order By: Relevance
“…Additionally, in yeast genetic backgrounds that support the formation of supersized LDs (such as ∆sei1 ∆pln1), the absence of ER-localized Psd1 may reduce the PE levels on the LD surface monolayer, attenuating the ability of small LDs to fuse with one another and generate supersized LDs (Fei et al, 2011). A non-mutually exclusive possibility is that altered PC/PE ratios at the ER in PSD-deficient cells influences LD protein targeting, which feeds back into influencing LD biogenesis or expansion (Caillon et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in yeast genetic backgrounds that support the formation of supersized LDs (such as ∆sei1 ∆pln1), the absence of ER-localized Psd1 may reduce the PE levels on the LD surface monolayer, attenuating the ability of small LDs to fuse with one another and generate supersized LDs (Fei et al, 2011). A non-mutually exclusive possibility is that altered PC/PE ratios at the ER in PSD-deficient cells influences LD protein targeting, which feeds back into influencing LD biogenesis or expansion (Caillon et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, LD biogenesis at the ER results in the formation of a hydrophobic oil phase surrounded by a phospholipid monolayer derived from the cytosolic leaflet of the ER. Such an architecture distinguishes LDs from other intracellular membrane-enveloped organelles, which are surrounded by phospholipid bilayers, and has profound consequences for phospholipid packing and protein localisation to LDs ( Caillon et al, 2020 ; Dhiman et al, 2020 ; Kory et al, 2015 ; Krahmer et al, 2011 ; Olarte et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As such, Type I LD proteins can translocate between the ER and LD monolayer via lipidic bridges connecting the two organelles (Wilfling et al, 2013). Elegant in vitro studies have suggested that LD localization promotes energetically favorable conformational changes within some proteins, and the movement of proteins to LDs from the ER network can even influence their enzymatic activities, or modulate their degradation (Caillon et al, 2020), (Chorlay and Thiam, 2020), (Leber et al, 1998), (Schmidt et al, 2013), (Ohsaki et al, 2006). A second mechanism of LD targeting occurs from the cytoplasm, where soluble proteins insert into the LD monolayer via a hydrophobic region, amphipathic helix, or lipid moiety.…”
Section: Introductionmentioning
confidence: 99%